Cover Feature: Iron Oxide Nanoparticles Functionalized with Fucoidan: a Potential Theranostic Nanotool for Hepatocellular Carcinoma (ChemBioChem 16/2022). (19th July 2022) - Geinguenaud, Frédéric; Sainte‐Catherine, Odile; Poirier, Florence; Besnard, Valérie; Haddad, Oualid; Chaubet, Frédéric; Lalatonne, Yoann; Lutomski, Didier; Sutton, Angela; Motte, Laurence
Abstract : Iron oxide nanoparticles (NPs) were functionalized with fucoidan, a natural sulfated polysaccharide. NP cellular uptake was quantified by magnetic measurement at various extracellular iron concentrations. Cell invasion and migration were reduced with NPs. Concomitantly, a high decrease of reactive oxygen species production related with a decrease of the matrix metalloproteinase‐9 activity and an increase of its expression was observed. Proteomic analysis showed that some fucoidan regulated proteins appeared related to protein synthesis, N‐glycan processing, and cellular stress. These results pave the way for USPIO‐fucoidan‐NPs as potential theranostic nanotools for hepatocellular carcinoma treatment. More information can be found in the Research Article by F. Geinguenaud et al.